2010
DOI: 10.1103/physrevb.81.184424
|View full text |Cite
|
Sign up to set email alerts
|

Ab initioconverse NMR approach for pseudopotentials

Abstract: We extend the recently developed converse NMR approach [T. Thonhauser, D. Ceresoli, A. Mostofi, N. Marzari, R. Resta, and D. Vanderbilt, J. Chem. Phys. 131, 101101 (2009)] such that it can be used in conjunction with norm-conserving, non-local pseudopotentials. This extension permits the efficient ab-initio calculation of NMR chemical shifts for elements other than hydrogen within the convenience of a plane-wave pseudopotential approach. We have tested our approach on several finite and periodic systems, find… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
73
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(78 citation statements)
references
References 39 publications
5
73
0
Order By: Relevance
“…To understand our sources of error, we first performed computations with a number of different pseudopotentials at the DFT level, followed by further computations at the GW level. Details of these computations, and of the other pseudopotentials used, 88,122,123,133,158,159 are given in the SI. In Table 18 GaAs, and Zn compounds show variation between different pseudopotentials derived with the same valence partition.…”
Section: A1 Effect Of Iodine Semicore States On Vip Resultsmentioning
confidence: 99%
“…To understand our sources of error, we first performed computations with a number of different pseudopotentials at the DFT level, followed by further computations at the GW level. Details of these computations, and of the other pseudopotentials used, 88,122,123,133,158,159 are given in the SI. In Table 18 GaAs, and Zn compounds show variation between different pseudopotentials derived with the same valence partition.…”
Section: A1 Effect Of Iodine Semicore States On Vip Resultsmentioning
confidence: 99%
“…As an alternative to linear response method, the theory of orbital magnetization via Berry curvature [147,148] can be used to calculate the NMR [149] and EPR parameters [150]. Specifically, it can be shown that the variation of the orbital magnetization M orb with respect to spin flip is directly related to the g-tensor: g µν = g e − 2 αS e µ · M orb (e ν ), where g e = 2.002319, α is the fine structure constant, S is the total spin, e are Cartesian unit vectors, provided that the spin-orbit interaction is explicitly considered in the Hamiltonian.…”
Section: Many-body Perturbation Theorymentioning
confidence: 99%
“…The specific pseudopotentials used were Si.pbe-tm-gipaw.UPF and O. pbe-tm-gipaw.UPF, which were downloaded from Davide Ceresoli's website. [23] DFT calculations using single-crystal XRD structures for the zeolites ITQ-4 [24] and Sigma-2 [6] were carried out to establish convergence as well as the relationship between calculated chemical shieldings and experimental chemical shifts (see Figure 3).…”
Section: Density Functional Theory Calculationsmentioning
confidence: 99%